2020
DOI: 10.1002/cbic.202000513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of i‐Motif Formation in the Serotonin Transporter‐Linked Polymorphic Region

Abstract: Neuropsychiatric disorders such as major depressive disorder (MDD) arise from a complex set of genetic and environmental factors. The serotonin transporter (SERT) is a key regulator of synaptic serotonin (5-HT), and its inhibition is an important pharmacological target for treating MDD. The SERT-linked polymorphic region (5-HTTLPR) contains two major variants (short and long) that have been implicated in modulating susceptibility to MDD by altering the level of expression of SERT. Both variants contain C-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have demonstrated that the DNA i -motif conformations can form at physiological pH in the nuclei of human cells as well as in the nuclei and chromosomes of invertebrates, corroborating the existence of i -motif structure in vivo. The prevalence of oligonucleotides with repetitive Cyt-rich sequences in genomic regions such as telomeres, centromeres, , and promoter areas of oncogenes have facilitated both in vitro and in vivo laboratory characterization of i -motif structures in these regions of the human genome and stimulated enormous interest in elucidating the functional roles of the i -motif in biological systems and its potential for use in nanotechnological applications. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that the DNA i -motif conformations can form at physiological pH in the nuclei of human cells as well as in the nuclei and chromosomes of invertebrates, corroborating the existence of i -motif structure in vivo. The prevalence of oligonucleotides with repetitive Cyt-rich sequences in genomic regions such as telomeres, centromeres, , and promoter areas of oncogenes have facilitated both in vitro and in vivo laboratory characterization of i -motif structures in these regions of the human genome and stimulated enormous interest in elucidating the functional roles of the i -motif in biological systems and its potential for use in nanotechnological applications. , …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of oligonucleotides with repetitive Cyt-rich sequences in genomic regions such as telomeres, 8 centromeres, 9,10 and promoter areas of oncogenes 11−13 have facilitated both in vitro and in vivo laboratory characterization of i-motif structures in these regions of the human genome 6 and stimulated enormous interest in elucidating the functional roles of the i-motif in biological systems 14 and its potential for use in nanotechnological applications. 13,15 Among the myriad of key questions concerning the biochemistry of nucleic acid i-motif conformations are the type and optimum number of protonated (Cyt)H + (Cyt) base pairs required to form a thermodynamically stable i-motif architecture and how this number is influenced by posttranscriptional modifications. These pertinent questions can be answered by first focusing on gaining an in-depth knowledge of the factors that govern the structures, stabilities, and dynamics of the noncovalent interactions that stabilize the i-motif.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The linkage polymorphic region of SERT contains two C-rich allelic variants that regulate susceptibility to depression by altering SERT expression levels. Both variants can form i-motifs; however, the mechanism requires further exploration ( Zhang et al, 2015 ; Thorne et al, 2021 ). As a key regulator of serotonin, i-motifs in the SERT-linkage polymorphic region will be an important pharmacological breakthrough for treating depression.…”
Section: Diseases Closely Associated With I-motifsmentioning
confidence: 99%
“…In addition to the TH promoter, the serotonin transporter-linked polymorphic region, which regulates serotonin transporter (SERT) gene expression, another important factor in neurological diseases and psychiatric disorders, also contains an i-motif-forming sequence [155]. This i-motif structure forms at neutral pH under molecular crowding conditions and could serve as an alternative target for SERT inhibition.…”
Section: Other Neurological Disordersmentioning
confidence: 99%